Face recognition in images - Bezdenezhnykh, A. O. (ТДАТУ, 2019)
The accuracy and efficiency of face recognition continues to grow. The system determines the identity faster and more accurately, avoiding erroneous identification. When used correctly, it will help increase public safety and maximize the potential and resources of users.
Keywords: recognition technology; the Viola-Jones method; face